A fluorogenic probe based on chelation–hydrolysis-enhancement mechanism for visualizing Zn2+ in Parkinson's disease models. Issue 14 (5th February 2019) - Zhang, Gaobin; Zhao, Yanfei; Peng, Bo; Li, Zheng; Xu, Chenchen; Liu, Yi; Zhang, Chengwu; Voelcker, Nicolas H.; Li, Lin; Huang, Wei
Abstract : Developing efficient methods for real-time detection of Zn 2+ level in biological systems is highly relevant to improve our understanding of the role of Zn 2+ in the progression of Parkinson's disease (PD). Abstract : Developing efficient methods for the real-time detection of Zn 2+ levels in biological systems is highly relevant to improving our understanding of the role of Zn 2+ in the progression of Parkinson's disease (PD). In this work, a novel Schiff base based Zn 2+ fluorescent probe (ZP ) was designed, synthesized and systematically investigated. A significant turn-on effect onZP upon the addition of Zn 2+ was observed, accompanied by a blue-shift of the fluorescence spectra.ZP is sensitive to Zn 2+ and has excellent selectivity against various biologically relevant cations, anions and amino acids. The sensing mechanism ofZP was studied by 1 H NMR, MS, single crystal X-ray diffraction and theoretical calculations. The results showed that the response ofZP to Zn 2+ was based on the chelation–hydrolysis-enhancement process. Upon bonding, Zn 2+ hydrolyzes the Schiff base to an aldehyde precursor, the resulting aldehyde further coordinates to Zn 2+ to form a more stable heterobimetallic complex leading to the emission enhancement and blue-shift.ZP was applied to imaging exogenous/endogenous Zn 2+ in live HeLa cells. Furthermore, we successfully measured the Zn 2+ levels using in vitro PD models, which provided a visualization method to better understand the relationship between Zn 2+ levels and PD development.